1955
DOI: 10.3189/002214355793702082
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Glacier Physics on the Penny Ice Cap, Baffin ISland, 1953. Part IV: The Flow of Highway Glacier

Abstract: The horizontal and vertical motions of eight points on the surface of Highway Glacier, Baffin Island are reported. The average horizontal speed below the lowest tributary glacier is 56 metres/year. The major part of this motion arises from the glacier sliding on its bed. The mean shear stress on the bed is practically constant and equal to about 0.9 bars, but it is much smaller beneath the retreating tongue. A measure of the retreat in the lower part of the glacier is obtained from the difference between the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…To assess the relative importance of internal deformation at different periods, we used historical and current measurements of ice thickness and surface slope at Highway Glacier (Ward, 1955) to compute expected deformation rates using a simplified form of Glen's flow law (Glen, 1955):…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the relative importance of internal deformation at different periods, we used historical and current measurements of ice thickness and surface slope at Highway Glacier (Ward, 1955) to compute expected deformation rates using a simplified form of Glen's flow law (Glen, 1955):…”
Section: Discussionmentioning
confidence: 99%
“…On Highway Glacier (Glacier 8), historical measurements allow a reconstruction of velocity changes over the past 58 years. From stake measurements made along two transverse profiles ∼0.87 km apart with a mean elevation of 760 m a.s.l., Ward (1955) estimated the mean annual surface velocity of the glacier to be 57 m a −1 over a 38 day period in July and August 1953 (Figs 3, 8). He also calculated the annual surface motion from the change in position of a medial moraine (situated between stakes A and B; Fig.…”
Section: Velocity Changes Through Timementioning
confidence: 99%
“…Before that, also in the USA, snow hydrological investigations had already been carried out (US Army Snow Hydrology, 1956). The earliest attempts at quantifying the glacial meltwater proportion of watershed yield were achieved by leveraging glacier mass balance, climate, and discharge data (Collier, 1958;Henoch 1971), while a glacier physics investigation was done on the Penny Ice Cap, Baffin Island (Ward, 1955). The surface hydrology of permafrost was summarized by Dingman (1971) and Church (1974), while in situ observations and cursory measurements were made in permafrost areas in the early half of the twentieth century by the Cold Regions Research and Engineering Laboratory (CRREL), USA (Sellmann, 1967).…”
Section: Origin Of the Cryohydrology Conceptmentioning
confidence: 99%
“…The genera l strike of th e crevasses is parallel to the direction of the maximum compressive axes at grids C, D and G , whereas the directions of the crevasses around grid H a re parallel to th e maximum shear directions, suggesting that the crevasses are produ ced by shear stresses. That crevasses should strike perpendicular to th e direction of the maximum tensile stress has been d emonstrated by Nye ( [952 , 1959), Ward (1955), Wu and Christensen (1964) and Ki zaki ( 1969). On the oth er hand, Taylor ( [963) showed that crevasses due to shear stress are ori entated at 45° to the direction of the maximum compressive stress.…”
Section: Physical Settingmentioning
confidence: 94%